Analysis of Learning Strategies and Media in the School Curriculum at SDIT Al-Marjan, Bengkulu City - Ari Wibowo; Nurlaili Nurlaili (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to evaluate the teaching strategies and learning media utilized in the implementation of the Kurikulum Merdeka at SDIT Al-Marjan in Bengkulu City, an Islamic-based school that integrates general education with religious values. A qualitative approach with a case study design was employed to examine the application of project-based learning (PjBL) and the use of digital technologies such as Google Classroom, Zoom, and social media as learning tools. The findings indicate that despite challenges such as limited infrastructure and teachers’ technological competencies, the school successfully fostered an interactive and adaptive learning environment. This was achieved through active teacher involvement, parental support in shaping students’ digital literacy, and the use of diverse learning media. In conclusion, contextual and collaborative teaching strategies and media play a vital role in supporting the successful implementation of the Kurikulum Merdeka, particularly in Islamic value-based schools in the digital era.